The associative movement of immigrants in the Comunidad Valenciana and its impact in the production of social capital - Masanet Ripoll, Erika; Santacreu Fernández, Oscar (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
The article offers an analysis of immigrant associations in the Region of Valencia through the theoretical perspective of social capital. Using a qualitative methodological approach, the research explores the implications of social capital generated by immigrant associations in the process of social inclusion and social development in the host society. The research results show that the type of social capital produced by associations, the limitations and weaknesses in such associations and the poor institutional receptiveness does not favor the development of a useful social capital that promotes the social integration of the immigrant population in the Valencian context
Keywords: Associations; Social capital; Immigrant population; Comunidad Valenciana